2019
DOI: 10.1142/s0217979219501923
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of MEMS-guided four beam piezoelectric transducers for energy harvesting and acceleration sensing

Abstract: In the present paper, guided four beam (G4B) piezoelectric transducers with enhanced sensitivities have been designed. Based on the suggested G4B structures, piezoelectric energy harvesters (PEHs) and acceleration transducers with higher voltages than their previously reported counterparts and with lower displacements than the single-cantilever PEHs (SC-PEHs) have been proposed. We have shown that it is possible to arrive at much more output voltages in comparison with the conventional PEHs by redesigning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It should be noted that the numerical simulation process used in this paper has been validated in our previous works on MEMS sensors and energy harvesters [32][33][34][35]. We have previously shown that our results for MEMS hydrophones are in a very close agreement with an experimentally fabricated hydrophone [36].…”
Section: Mems Diaphragm Hydrophonesupporting
confidence: 71%
“…It should be noted that the numerical simulation process used in this paper has been validated in our previous works on MEMS sensors and energy harvesters [32][33][34][35]. We have previously shown that our results for MEMS hydrophones are in a very close agreement with an experimentally fabricated hydrophone [36].…”
Section: Mems Diaphragm Hydrophonesupporting
confidence: 71%
“…Microstructures based on silicon substrates are, therefore, a key issue in bulk micromachining technology. Bulk Si three-dimensional (3D) micromachined structures (e.g., cavities, grooves, through holes, and mesas) have been an area of extensive research in microelectromechanical systems (MEMS) [1][2][3][4]. From the fabrication point of view, etching techniques are divided into two main categories: deep reactive ion etching (DRIE) and anisotropy wet etching.…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration measurement, as an important technical means to monitor the medium-frequency and high-frequency vibration performance of engineering structures, can reflect the vibration situation of several large-scale structures [4,5] . At this stage, the electric sensor is the main instrument for acceleration measurement, and is characterized with low cost, small volume and relatively mature technology [6] ; however, in the complex situations, it also has disadvantages of poor circuit stability, large signal noise and being is susceptible to electromagnetic interference [7,8] . Compared with the traditional electrical acceleration sensor, FBG acceleration sensor has the better sensitivity and linearity, better anti-electromagnetic interference and stability, easier distribution and measurement based on several parameters [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%